MODEL OPTIMASI WAKTU TUNGGU LAMPU LALU LINTAS DENGAN METODE WEBSTER - Nasya Nasya; Devitasari Simamora; Citra Amanda Putri; Ria Sagita Ningsi (MATHunesa: Jurnal Ilmiah Matematika, 2025)
In big cities like Medan, traffic jams are a problem that often occurs, especially in the SM Road T-junction area. King. To overcome this problem, a study was carried out that combined the use of compatible graph modeling and the Webster method. The application of compatible graphs helps in determining the phases of traffic lights and identifying lanes that can operate simultaneously. Meanwhile, the Webster method is used to calculate the ideal waiting time for vehicles. This study resulted in the optimization of two traffic light phases with a total cycle time of 344 seconds, where there was an increase in the duration of the green light on each road section. This system is proven to be more effective because it provides a longer green light flash time compared to red lights. Keywords: Traffic, compatible graph, Webster's method.